Relation Between Rates of Geriatric Suicide and Consumption of Alcohol Beverages in European Countries - Leo Sher (The Scientific World Journal)
Among older adults, suicide is a significant and persistent health problem. The highest suicide rate is found among white men aged 65 years and older. The causes of elder suicide are multifaceted. Although no predominate factor precipitates or explains geriatric suicide, alcohol is strongly linked to suicide attempts and completions. This study examined the relationship between rates of suicide in 65- to 74-year-olds and per capita consumption of alcoholic beverages in European countries. Data on suicide rates in 65- to 74-year-olds and per capita consumption of alcoholic beverages were obtained from the World Health Organization databases. Correlations were computed to examine relationships between suicide rates in 65- to 74-year-old males and females and per capita consumption of beer, wine, and spirits in the general population in 34 European countries. There was a positive correlation between suicide rates in 65- to 74-year-old males and per capita consumption of spirits. No correlations between suicide rates in 65- to 74-year-old males and per capita consumption of beer or wine were found. We also found no correlations between rates of suicide in 65- to 74-year-old females and per capita consumption of beer, wine, or spirits. The results of this study are consistent with reports that consumption of spirits is associated with suicide events. It is to be hoped that this paper will stimulate further studies that are necessary to clarify the relation between suicide rates in different age groups and consumption of alcoholic beverages, and attract more attention to the problem of geriatric suicide.